TERAPI ISLAM SEBAGAI ALTERNATIF PENANGGULANGAN PERILAKU MENYIMPANG REMAJA - Alief Budiyono (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2011)
Juvenile deliquency is a pidure of antisodal personality or behavior disorder of adolescents. To help young people achieve optimal growth and avoid deviant behavior can be done through retuming to the nature of teens as the obedient servant of God worship. Due to retuming them to do the worship to God and always run His rules corredly and implement the prophet's traditions, it is expeded that teenagers will always behave well and will be spared from deviant behaviors.